The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/2156347
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Satisfaction with Antenatal Care and Associated Factors among Pregnant Women in Hossana Town

Abstract: Background. A woman’s satisfaction with antenatal care service has immediate and long-term impacts on maternal and her baby’s health. It also ensures further use of service. However, it is not well studied in Ethiopia in general and at the southern region in particular. Objective. The main objective of this study is to assess the level of a maternal satisfaction with antenatal care services and associated factors. Methods. An institution-based cross-sectional study that involves both quantitative and qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 23 publications
4
23
0
1
Order By: Relevance
“…All of them are cross-sectional by design. Six of the included studies were from Southern Nation Nationalities And Peoples Region (SNNPR) [18][19][20][21][22][23], four from Oromia [24][25][26][27], one from Amhara region [28], one from Harari [29], and one from Addis Ababa city [30]. Regarding the response rate, all studies had a good response rate (>88%) (Table 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…All of them are cross-sectional by design. Six of the included studies were from Southern Nation Nationalities And Peoples Region (SNNPR) [18][19][20][21][22][23], four from Oromia [24][25][26][27], one from Amhara region [28], one from Harari [29], and one from Addis Ababa city [30]. Regarding the response rate, all studies had a good response rate (>88%) (Table 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…All of them are cross-sectional by design. Six of the included studies were from Southern Nation Nationalities And Peoples Region (SNNPR) (15,(20)(21)(22)(23)(24), four from Oromia (25-28), one from Amhara region (29), one from Harari (30), and one from Addis Ababa city (31). With regard to the response rate, all studies had a good response rate (> 88%) (Table 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The association between maternal age and antenatal care service satisfaction was examined based on the ndings from three studies (22,26,31). The pooled odds ratio (AOR: 0.91 and 95% CI: 0.66-1.25) showed that antenatal care service satisfaction was not affected by the age of the mother.…”
Section: Association Between Maternal Age and Antenatal Care Service Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations